Inhibition of herpes simplex virus type 1 by copper oxide nanoparticles - Tavakoli, Ahmad; Hashemzadeh, Mohammad Sadegh (Journal of virological methods, 2020)
•Copper oxide (CuO-NPs) nanoparticles significantly inhibit HSV-1 infection.•The inhibition occurs when CuO-NPs are added after virus adsorption to the cells.•100 μg/mL of CuO-NPs leads to 83.3% reduction in HSV-1 viral load. There are accumulating reports of the emergence of drug-resistant strains of HSV-1 that have become a barrier to successful treatment of HSV-1 infection. Therefore, there is a pressing need to identify and evaluate alternative antiherpetic agents. The aim of the present study was to investigate the effect of copper oxide nanoparticles (CuO-NPs) on HSV-1 infection. The MTT assay was applied to examine the cytotoxic effects of CuO-NPs on Vero cells. Antiherpetic potency was determined using the TCID50 and quantitative Real-Time PCR assays. To evaluate the inhibitory impact of CuO-NPs on the expression of viral antigens, an indirect immunofluorescence assay (IFA) was performed. Acyclovir was used as a reference drug in all experiments. Exposure of HSV-1 with CuO-NPs at the highest non-toxic concentration (100 μg/mL) resulted in 2.8 log10 TCID50 reduction in infectious virus titer as compared with virus control (P < 0.0001). This concentration of CuO-NPs was associated with 83.3% inhibition rate, which was estimated based on the HSV-1 viral load compared to virus control. Our findings demonstrated that CuO-NPs are associated with a significant antiviral potency against HSV-1. This feature shows strong potential for CuO-NPs to be used in topical formulations for the treatment of orolabial or genital herpetic lesions.